Pengaruh Pemahaman Peraturan Perpajakan Terhadap Kepatuhan Wajib Pajak Studi Kasus: di KPP Pratama Cilegon - Angga Nugraha; Dian Febrianti; Novan Ekkiwinatha; Lisa Arisa; Annissa Pratiwi; Khairun Nisa; Romadhon Romadhon (Ikatan Da'i Indonesia, 2025)
This study examines the effect of understanding tax regulations on taxpayer compliance at the Cilegon Primary Tax Office (KPP Pratama Cilegon). This research is motivated by the importance of improving taxpayer compliance to optimize state revenue, with the level of understanding of tax regulations identified as a key influencing factor. This study employs a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 60 registered individual taxpayers at KPP Pratama Cilegon. Data were analyzed using validity and reliability tests, classical assumption tests, simple linear regression analysis, and t-tests, processed with SPSS version 27. The results indicate that understanding tax regulations has a positive and significant effect on taxpayer compliance. The t-value was 7.710, which is greater than the t-table value of 2.001, with a significance level of 0.000 (p < 0.05). The coefficient of determination (R²) of 0.506 shows that understanding of tax regulations explains 50.6% of the variation in taxpayer compliance, while the remaining 49.4% is explained by other factors not included in this study. These findings confirm that the higher a taxpayer’s understanding of tax regulations, the higher their compliance in fulfilling tax obligations.